2019
DOI: 10.1088/1742-6596/1301/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

On two experiments with falling chains

Abstract: The article considers paradoxical results of metal chain movement that do not agree with classical theoretical models. We present the results of experiments with the falling U-folded chain and with chain fountain. The velocity and acceleration of chain motion were measured and estimated. The trajectory of the fountaining chain links has been investigated experimentally. A comparison of the experimental data with existing theoretical models is made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The author also reported that the tip of the chain is falling faster than the time required for its free fall. Domnyshev et al [24] used two different types of chains with different diameter to investigate the free falling of the U-folded chain. High-speed imaging was used to record the experiment with rate 500 fps.…”
Section: Introductionmentioning
confidence: 99%
“…The author also reported that the tip of the chain is falling faster than the time required for its free fall. Domnyshev et al [24] used two different types of chains with different diameter to investigate the free falling of the U-folded chain. High-speed imaging was used to record the experiment with rate 500 fps.…”
Section: Introductionmentioning
confidence: 99%